Zubererazko herskarien azterketa akustikoa - Mounole, Céline (Anuario del Seminario de Filología Vasca "Julio de Urquijo", 2004)
This is an acoustic study of the word initial aspirated and non-aspirated voiceless consonant stops ofthe Basque dialect of Zuberoa. Using data from four speakers aged 66 to 80, we measured the Voice Time (hence, VOT) of the voiceless stops of such dialect. Those measurements showed that the Zuberoan dialect of Basque has two sets of consonant stops, the VOT being larger in the aspirated stops than in the non-aspirated ones. Moreover, we observed that the accent does not affect the VOT of each set of stops (unlike in English, for example). Finally, VOT is known to vary with place of articulation. Besides, as expected among the aspirated and non-aspirated stops, we find the scale k > t > p with the velar stop triggering the largest VOT measurements.